The Impact of Gadget Using Analytical on Toddler (Research In TK Tunas Harapan Salo) - Rusnedy, Hidayati; Hidayat; Lailatul Syifa Tanjung; Resy Kumala Sari (Journal of Engineering Science and Technology Management (JES-TM), 2023)
The use of gadgets, especially smartphones and tablets, for young children has now become a public concern. This is because gadgets have become a necessity for society and even children. Gadgets are technology that have very interesting applications and features, such as games and videos which children really like. Most parents do not supervise and regulate their children's use of gadgets and sometimes parents are not aware that their children are addicted to gadgets. This research aims to analyze the influence of gadget use on young children, with research subjects being carried out on Tunas Harapan Salo Kindergarten students. The results of the research show that the negative impacts are more pronounced in Tunas Harapan Kindergarten students where they show attitudes such as being easily emotional, imitating movements and language in the games or videos they see, and when using gadgets, they don't care and ignore the surrounding conditions, they don't care. care if called while playing gadget. However, even though the negative impacts are more visible, there are several positive impacts from using gadgets, namely that they can learn traditional gymnastics and dance movements through YouTube videos